Notoginsenoside R1 attenuates oxidative stress‐induced osteoblast dysfunction through JNK signalling pathway. Issue 24 (16th November 2021) - Li, Xumin; Lin, Haiyan; Zhang, Xiaorong; Jaspers, Richard T.; Yu, Qihao; Ji, Yinghui; Forouzanfar, Tim; Wang, Dongyun; Huang, Shengbin; Wu, Gang
Abstract: Oxidative stress (OS)‐induced mitochondrial damage and the subsequent osteoblast dysfunction contributes to the initiation and progression of osteoporosis. Notoginsenoside R1 (NGR1), isolated from Panax notoginseng, has potent antioxidant effects and has been widely used in traditional Chinese medicine. This study aimed to investigate the protective property and mechanism of NGR1 on oxidative‐damaged osteoblast. Osteoblastic MC3T3‐E1 cells were pretreated with NGR1 24 h before hydrogen peroxide administration simulating OS attack. Cell viability, apoptosis rate, osteogenic activity and markers of mitochondrial function were examined. The role of C‐Jun N‐terminal kinase (JNK) signalling pathway on oxidative injured osteoblast and mitochondrial function was also detected. Our data indicate that NGR1 (25 μM) could reduce apoptosis as well as restore osteoblast viability and osteogenic differentiation. NGR1 also reduced OS‐induced mitochondrial ROS and restored mitochondrial membrane potential, adenosine triphosphate production and mitochondrial DNA copy number. NGR1 could block JNK pathway and antagonize the destructive effects of OS. JNK inhibitor (SP600125) mimicked the protective effects of NGR1while JNK agonist (Anisomycin) abolished it. These data indicated that NGR1 could significantly attenuate OS‐induced mitochondrial damage and restore osteogenic differentiation of osteoblast via suppressing JNK signalling pathway activation, thus becoming a promising agent in treating osteoporosis.